Importance of Drug Utilization Evaluation Studies In Patient Health Care - Ashok, Purnima; Subramanian, Vijeesh Tholur (Indian Journal of Pharmacy Practice)
Rational drug use is an important factor to be checked for the optimal benefit of drug therapy in patient care.1 In India, many factors like illiteracy, poverty, use of multiple health care systems, drug advertising and promotion, sale of prescription drugs without prescription, competition in medical and pharmaceutical market place and limited availability of drug information are the main reasons for not achieving the optimal health care.6 Inappropriate use of drug also leads to increased cost of medical care, antimicrobial resistance, adverse effects and patient mortality. Hence the drug utilization evaluation (DUE) studies becomes one of the potential tools in evaluation of health system.1,4 Drug utilization studies focuses on factors related to prescribing, dispensing, administering and taking of medication and associated events.1